2014
DOI: 10.1103/physreva.89.013421
|View full text |Cite
|
Sign up to set email alerts
|

Weak-field asymptotic theory of tunneling ionization in many-electron atomic and molecular systems

Abstract: The weak-field asymptotic theory of tunneling ionization in an external static uniform electric field [Tolstikhin et al., Phys. Rev. A 84, 053423 (2011)] is extended to many-electron atomic and molecular systems treated in the frozen-nuclei approximation. The leading-order term in the asymptotic expansion of the ionization rate in the value of the field F for F → 0 is obtained. The resulting formulas express in terms of properties of the unperturbed system. The most essential difference from the one-electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 76 publications
(220 reference statements)
4
66
1
1
Order By: Relevance
“…48 In the case of the non-degenerate HOMO-1 (a 1 symmetry) U = 0 by symmetry and V is obtained as described above. The HOMO-2 of all CH 3 X molecules are degenerate (e symmetry) and were treated in the same way as the HOMO.…”
Section: 18mentioning
confidence: 99%
“…48 In the case of the non-degenerate HOMO-1 (a 1 symmetry) U = 0 by symmetry and V is obtained as described above. The HOMO-2 of all CH 3 X molecules are degenerate (e symmetry) and were treated in the same way as the HOMO.…”
Section: 18mentioning
confidence: 99%
“…Within the SAEA, the present tunneling data provided for H 2 O are of unprecedented precision. It will be interesting to see in the future if the inclusion of many-electron effects [26] has an impact on the tunneling ionization of H 2 O.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison with exact results for atoms within the SAEA showed that these terms extend the region of applicability of the WFAT at the quantitative level toward stronger fields, practically up to the boundary between tunneling and over-the-barrier ionization regimes. Very recently, extensions of the WFAT to account for the effects of nuclear motion were considered [24,25] and a generalization to many-electron systems in the frozen-nuclei approximation was developed [26].…”
Section: Introductionmentioning
confidence: 99%
“…1 and the Keldysh parameter γ for this state should be smaller than 1 [33]. Apart from numerically solving the TDSE [34], methods such as the molecular Ammosov-Delone-Krainov theory [35,36] and the weak-field asymptotic theory [37][38][39][40][41] have been developed to obtain analytical formulas for the tunneling ionization rates for molecules. The tunneling ionization rates from the two lowest electronic states in H 2 + , i.e, the 1sσ g and 2pσ u states, were ab initio values taken from Ref.…”
Section: A the Mcwp Approachmentioning
confidence: 99%